Comparison of the Effectiveness of 32% and 40% Ethanol Extracts of Areca Nut (Areca catechu L.) in Inhibiting the Growth of Candida albicans on Heat-Cured Acrylic Resin Dentures - Fernanda, Bella; Sinamo, Sopan; Elyas, Elwanda El Akbar (Publikasi Indonesia, 2026)
Complete dentures made from heat-polymerized acrylic resin are widely used for their good esthetics and biocompatibility, but their porous nature can promote the growth of Candida albicans and lead to denture stomatitis. While chemical cleansers such as alkaline peroxide are effective, long-term use may damage the denture material, highlighting the need for safer natural alternatives, including the ethanolic extract of areca nut (Areca catechu L.) with antimicrobial properties. This study aimed to evaluate and compare the inhibitory effectiveness of 32% and 40% areca nut ethanolic extracts against the growth of Candida albicans on heat-polymerized acrylic resin denture bases. This research was an in vitro experimental laboratory study with a post-test only control group design. A total of 24 acrylic resin specimens were divided into four groups: 32% areca nut extract, 40% areca nut extract, alkaline peroxide as a positive control, and distilled water as a negative control. After treatment, the number of Candida albicans colonies was counted and statistically analyzed. The results showed a significant difference among groups (p < 0.05). Both concentrations reduced fungal colonies, with the 40% extract showing greater inhibitory effectiveness than the 32% extract, although its antifungal activity remained lower than alkaline peroxide. In conclusion, the ethanolic extract of areca nut, especially at a 40% concentration, shows potential as a natural denture cleanser to inhibit Candida albicans growth